(3GdTaG HJYQja Mbhb GdeUWais - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HESeg GdCSeI CeG HYO aEfc cQQJ Ydi GdSDGd ai eLehY jJVef GdJYQja HbOQ GdeUWai Ydjg GdUdGI hGdSdGe aGYde Efc MedJfi ef Pdc CeQkG EeQG s
(3BNQgG (B:s
(3gfG GfJgi Gdbhd efG aejG MQQfGg hfMeOg JYGdi Ydi eG gOi Edgj ef LeYg hCdge hgh MSHfG hfYe Gdhcjd , hUdGJg Ydi SjOfG eMeO fHjfG eMeO hSde JSdjekG cKjQkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQi s
(3Ydi GdfSNI JbjOGJ s
(3HChdgG JedcGJ CbOegG SfI (B1106 (3g` s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs